Epithelial inclusion cysts of the frontal bones in three horses. (27th August 2013) - Gunnarsdottir, H.; Chiers, K.; Praet, M.; Saunders, J.; Schauvliege, S.; Vlaminck, L.
Summary In this article, development of a fluctuating swelling in the middle of the frontal region is reported in 3 horses. Clinical and radiological examinations showed them to be palpably soft, nonpainful, well circumscribed and homogeneous. The diagnosis of a cyst‐like lesion is based on centesis and histology. This report describes the clinical features, surgical treatment, outcome and histological findings in all 3 cases.